COVID-19’s Effect on Crisis Intervention Team Calls for Service in Houston - R. Nielson, Kyler (American journal of criminal justice, 2024)
Research examining the effects of COVID-19 on the criminal legal system—including the demand for police services—is accumulating. However, few empirical inquiries have sought to examine the pandemic’s effect on mental health and wellbeing by analyzing calls for service (CFS) involving emotionally disturbed persons (EDP). This study examines CFS received pre- and post-pandemic by Houston’s crisis intervention team (CIT). By examining visual trends and using interrupted time-series analysis (ITSA), we analyze COVID-19’s immediate and long-term effects. In the current study we examine three distinct call types: (1) Risk to others; (2) Risk to self; and (3) Welfare calls. Findings demonstrate significant increases in the overall CFS after the implementation of the initial stay-at-home order in Houston, with some differences in trends based on call type. These findings further our understanding of COVID-19’s impact on mental health and wellbeing during the pandemic through the lens of the increased demand for police services. Specific implications for the study site department are discussed, and to the extent possible, general implications for other departments with CIT programs.